Surveillance Tracking In Busy Environment - Ahmad Shazuan bin Abdul Rahim, Ahmad Shazuan (Universiti Teknologi Petronas, 2009)
This study discusses the research done and understanding of the chosen topic, which is "Surveillance Tracking in Busy Environment". The objective of this project is to develop an algorithm to do surveillance tracking with capability to track multiple objects. With considering the fact that surveillance in public area is quite important, this tracking system is aimed to produce a low-cost system that can track multiple objects movement by using a camera and a computer. The camera will be the input to capture everything in the sight and the captured image data will be sent to the computer to be analyzed by the tracking system installed in the computer.